Sustainable composite development: Novel use of human hair as fiber in concrete (2020)
In the present era, to recycle waste and to reduce environmental pollution is the main objectives of sustainable development. Many researchers are working on new techniques and thinking for innovation in the field of concrete technology by utilizing the waste material in concrete. This research aims to check the effect of a human hair (waste material) as fiber on the fresh, physical and mechanical properties of concrete with 0%, 1%, 2%, 3%, and 4% of human hair by volume of cement. In this regard, a total of 180 concrete specimens (cubes, cylinders, and prisms) was made and cured after 7th, 28th, and 90th day. The result indicated that the compressive strength was enhanced by 8.15 % at 1% human hair after 28 days as indirecttensile strength and flexural strength were improved by 21.83 % and 12.71 % at 2% of human hair after 28 days, respectively. Also, the density of concrete gets reduced with rising in the content of human hair, and water absorption is improved, as the content of human hair increases after 28 days, respectively. Besides, the modulus of elasticity increased with the inclusion of human hair after every curing period, and drying shrinkage of concrete is minimized with the addition of human hair as fibers in concrete at 40 days. The slump value was reduced as the content of human hair increased.